River Water Quality and its Relation with Air Quality: A Long-Term Case Study in a Remote and Pristine NW Italian Headwater Catchment - Casazza, Marco; Maraga, Franca; Liu, Gengyuan; Lega, Massimiliano; Turconi, Laura; Ulgiati, Sergio (Journal of Environmental Accounting and Management, 2026)
This paper analyses the water quality characteristics of a remote and pristine basin, the Gallina small catchment, located in the Piemonte Region (NW Italy). In particular, the ion content of river water and precipitation are assessed for two distinct periods (October-December of years 1992 and 2011). These time frames are characterized by a change of air quality management rules for the study area which came into force after year 2000. Furthermore, late Autumn months, which are considered in this study, are characterized by a peak of recorded precipitations in the area under study. Moreover, this is a period of the year where atmospheric emission intensity and distribution are greater with respect to Spring and Summer. The chemical nature of the monitored water body was assessed through the use of Piper diagram. Research found evidence of erosional processes, which chemically altered the water compared to the quality of precipitation. The signature of air chemistry was also evident, through a shift to less sulphate, after the change of air quality regulations introduced in year 2000. The presence of marine ions, in case of major weather perturbations, typical of the late Autumn in the monitored area, was recorded. This fact was particularly evident for the month of November 2011, in association to a major flooding event occurred in the Piemonte Region. The presence of a minor ionic component, associated to rainfall waters, depending upon soil particle resuspension and transport was also detected. Finally, the prevailing origin of the measured ions was defined. The results show the importance of improved management actions, which should be taken in order to further reduce the trans-boundary atmospheric pollution, which constitutes a threat to water quality and a further element of indirect water pollution transfer across different areas.